Pengaruh Empowerment Leadership Terhadap Kinerja Guru di SMP Negeri Se Kecamatan Mesuji - Wahyuti, Yuli; Lestari, Neta Dian (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to analyze the effect of empowerment leadership on teacher’s performance in junior high schools in Mesuji District. The approach used is a literature review, by collecting and analyzing various relevant research results in national journals related to empowerment leadership and teacher’s performance. Through a literature review, this study discusses the concept of empowerment leadership, which involves empowering teachers to make decisions, support in developing competencies, and increasing work motivation. This study collects literature from national journals published in the last four years, with an analysis focused on research results that measure the impact of empowerment leadership on improving teacher performance, both directly and indirectly. The results of the study indicate that empowerment leadership has a significant positive effect on teacher’s performance, especially in terms of motivation, job satisfaction, and commitment to the school. Teachers who feel empowered by the principal tend to have better performance, as indicated by improved teaching quality and involvement in school activities. The novelty of this study lies in its focus on the local context in junior high schools in Mesuji District, which has so far been underrepresented in the literature. The contribution of this research is to provide a clearer picture of the importance of empowerment leadership in improving teacher’s performance, which can be a reference for regional education policy makers in designing school leadership programs.